Odpowiedź :
Odpowiedź:
2x + 3 = 11
2x = 11 - 3
2x = 8
x = 4
3x - 5 = 13
3x = 13 + 5
3x = 18
x = 6
8 + 4x = 26
4x = 26 - 8
4x = 18
x = 4,5
3x - 4 = 12
3x = 12 + 4
3x = 16
x = [tex]5\frac{1}{3}[/tex]
2x + 2 = 8
2x = 8 - 2
2x = 6
x = 3
-5x + 3 = -12
-5x = -12 - 3
-5x = -15
-x = -3
x = 3
Pozdrawiam, miłego wieczoru
Odpowiedź:
2x+3 = 11 |-3
2x = 8 |:2
x = 4
2) 3x - 5 = 13 |+5
3x = 15 | : 3
x = 5
3) 8 + 4x = 26 | - 8
4x = 18 | : 4
x = 4 i 1\2
4) 3x - 4 = 12 | + 4
3x = 16 | : 3
x = 5 i 1\3
5) 2x + 2 = 8 | -2
2x = 6 | : 2
x = 3
6) -5x + 3 = -12 | -3
-5x = -15 | : (-5)
x = 3
Szczegółowe wyjaśnienie: